PERAN GURU AQIDAH AKHLAK DALAM MENDIDIK KARAKTER PESERTA DIDIK SEBAGAI PENCEGAH KENAKALAN PELAJAR DI MTS MIFTAKHUL ULUM 01 PUJON - Fahmi Awalul Ihsan; Imam Safi’i; Dwi Fitri Wiyono (VICRATINA, 2022)
Student delinquency is an act or deed carried out by students either alone or in groups whose nature is contrary to school regulations. Delinquency of students, especially in the school environment, is still a problem at Mts Miftakhul Ulum 01 school, if this delinquency is carried out continuously, it will certainly harm the students themselves and will disrupt the learning process. The Character of Students as a Prevention of Student Delinquency at MTS Miftakhul Ulum 01 Pujon, in this case the researcher uses descriptive qualitative methods. Regarding the results obtained, the teacher must be able to maximize the delivery of Aqidah khlak material and choose learning methods according to the needs of students, habituation of ubudiyah Islamiyah, provide examples of good exemplary attitudes, character education programs for students will be given material about character education.